Behavioral Patterns, Rather Than Environmental Factors, Shape the Energy Balance of Wintering Chinese Mergansers (Mergus squamatus) in Huangshan - Chao Yu; Hao Zheng; Yu Luo; Mengxue Guo; Shiqi Wang; Xuanshuo Qi; Qun Li; Zhonghai Lv (Ecology and Evolution, 2025)
ABSTRACT Animal energy intake and expenditure strategies in response to environmental fluctuations have been widely studied. Optimal foraging theory (OFT) is the dominant framework in this field; however, studies addressing the OFT in endangered waterbird species are lacking. To address this gap in our knowledge, we collected behavioral data and investigated habitat variables that influence the energy intake and expenditure of the endangered Chinese merganser (Mergus squamatus ) in the Changjiang, Shuaishui, and Jianjiang Rivers in Huangshan, Anhui Province, China, from January to March 2023. The results revealed a correlation between net energy, energy intake, and energy expenditure rates. Successful foraging frequencies increased net energy intake and energy intake rates and reduced the feeding time. Furthermore, running on water, flying, diving, and average fish weight increased energy expenditure rates, whereas successful foraging frequencies, vigilance, resting, fish biomass, river width, and eye‐submerging decreased energy expenditure rates. Chinese mergansers adjusted behavioral time allocations to regulate energy intake, energy expenditure, and net energy intake rates. The net energy and energy intake rates were independent of environmental factors, excluding energy expenditure rates and average fish weight, fish biomass, and river width. The behaviors influencing the energy balance were modified in response to environmental factors. However, environmental factors did not affect the energy levels through behaviors. These results elucidate the energy intake, expenditure, and balance strategies used by Chinese mergansers in response to variations in their wintering habitats. They provide valuable insights for conserving and managing habitats critical to the survival of Chinese mergansers and other waterbird species.